2011
DOI: 10.1002/jbm.b.31837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spinal instrumentation rod bending characteristics for in‐situ contouring

Abstract: Bending characteristics were studied in rods used for spinal instrumentation at in-situ contouring conditions. Five groups of five 6 mm diameter rods made from: cobalt alloy (VITALLIUM), titanium-aluminum-vanadium alloy (SDI™), β-titanium alloy (TNTZ), cold worked stainless steel (STIFF), and annealed stainless steel (MALLEABLE) were studied. The bending procedure was similar to that typically applied for in-situ contouring in the operating room and included two bending cycles: first--bending to 21-24° under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…This intraoperative bending of the rod introduces cracks or dents in the material, which can reduce the endurance limit of the rod, also termed the “notch effect”. Slivka et al [ 32 ] found that the endurance limit of CoCr was at least 25% higher than UHSS, SS, or TI in response to repetitive bending whereas Noshchenko et al [ 33 ] showed the highest “springback” (or yield strength) in Ti rods compared to SS. Wedemeyer et al [ 34 ] in a bovine model, confirmed that Tis can withstand higher strains and yield than the relatively brittle SS before failure occurs after bending.…”
Section: Rod Materialsmentioning
confidence: 99%
“…This intraoperative bending of the rod introduces cracks or dents in the material, which can reduce the endurance limit of the rod, also termed the “notch effect”. Slivka et al [ 32 ] found that the endurance limit of CoCr was at least 25% higher than UHSS, SS, or TI in response to repetitive bending whereas Noshchenko et al [ 33 ] showed the highest “springback” (or yield strength) in Ti rods compared to SS. Wedemeyer et al [ 34 ] in a bovine model, confirmed that Tis can withstand higher strains and yield than the relatively brittle SS before failure occurs after bending.…”
Section: Rod Materialsmentioning
confidence: 99%
“…The first notion states that primary contouring or metal bending (including the use of French benders) has shown to weaken metal and decrease fatigue strength [ 20 , 21 ]. Further, repeated bending or rod contouring to an extreme angle has been hypothesized to decrease rod fatigue strength [ 20 25 ]. While biomechanical studies have shown a link between “excessive contouring” and decreased fatigue strength, no clinical study to date has confirmed if this “excessive contouring” poses a significant risk in real-world surgical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were conducted in different countries across continents that increase the external validity of the study. Four studies were done in USA [ 21 , 23 25 ], two studies in France [ 12 , 16 ], two studies in South Korea [ 17 , 18 ], two studies in Japan [ 19 , 22 ], and one study in Malaysia [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies reported the different outcomes of interest concerning our study questions. Four studies compared correction rate [ 12 , 16 , 19 , 20 ]; five studies compared rod fracture [ 17 19 , 24 , 25 ]; three studies compared thoracic kyphosis [ 12 , 16 , 20 ], proximal junctional kyphosis [ 12 , 17 , 18 ], and fatigue life [ 21 23 ] each; two studies compared lumbar lordosis [ 12 , 16 ] and bending stiffness [ 22 , 23 ] each. Studies comparing similar outcomes were analyzed together in the same forest plot.…”
Section: Resultsmentioning
confidence: 99%